Sodium effect on self-organization of amphiphilic carboxylates: Formation of structured micelles and superlattices - Rosenlehner, Karin; Schade, Boris; Böttcher, Christoph; Jäger, Christof; Clark, Timothy; Heinemann, Frank Wilhelm; Hirsch, Andreas (Chemistry - A European Journal, 2010)
Not only the self-aggregation of dendritic polycarboxylates intostructurally persistent micelles, but also that of the micelles themselves into superlatticesis controlled by alkali-metalcounterions and shows a pronounced sodium effect. Our combined experimental and computational work has revealed the formation of superlattices for the first time. The behavior of a variety of amphiphilic carboxylates and the different effects of the alkali cations Li, Na, and K have been investigated by conductivity measurements, cryogenic transmission electron microscopy (cryo-TEM), and molecular-dynamics (MD) simulations. Together, these show that sodium salts of the amphiphiles give the most stable micelles, followed by lithium and potassium. Our results suggest that ion multiplets in bridging positions, rather than contact ion pairs, are responsible for the enhanced stability and the formation of hexagonally ordered superlattices with sodium counter ions. Potassium ions do not form such ion multiplets and cannot therefore induce aggregation of the micelles. This sodium effect has far-reaching consequences for a large number of biological and technical systems and sheds new light on the origin of specific-ion effects. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.